2022
DOI: 10.3390/nu14020289
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Quality of Women of Reproductive Age in Low-Income Settings: A Cross-Sectional Study in Kyrgyzstan

Abstract: Dietary diversity and adequate nutrient intake are essential for conducting a healthy life. However, women in low-income settings often face difficulties in ensuring dietary quality. This research assessed relationships between the dietary diversity, nutrient adequacy, and socio-economic factors among women of reproductive age (WRA) in Kyrgyzstan. A cross-sectional study was undertaken in four locations, including two rural and two urban areas in the north and south of Kyrgyzstan. A survey with pre-coded and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…To our knowledge, we are the first to report a hidden hunger assessment scale especially for high school students. Previous studies have revealed a positive correlation between dietary diversity and micronutrient adequacy, and dietary diversity indicators including dietary diversity scores (DDS) and food insecurity (FI) assessment tools including household food security survey (HFSS) have been used for screening hidden hunger [48][49][50]. However, the possible impact of bioaccessibility also needs to be considered in the assessment, which seems to be neglected in previous research [42].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, we are the first to report a hidden hunger assessment scale especially for high school students. Previous studies have revealed a positive correlation between dietary diversity and micronutrient adequacy, and dietary diversity indicators including dietary diversity scores (DDS) and food insecurity (FI) assessment tools including household food security survey (HFSS) have been used for screening hidden hunger [48][49][50]. However, the possible impact of bioaccessibility also needs to be considered in the assessment, which seems to be neglected in previous research [42].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, evidence supports dietary diversification for optimal nutrition and health ( 15 , 16 ). Consumption of diverse diets is central to achieving and preserving nutrient adequacy throughout the life course ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, evidence supports dietary diversification for optimal nutrition and health ( 15 , 16 ). Consumption of diverse diets is central to achieving and preserving nutrient adequacy throughout the life course ( 15 , 16 ). Inadequate dietary quantity and quality result in deficiencies of essential nutrients, particularly during pregnancy and lactation ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies mentioned that dietary diversity in urban areas is higher compared to rural (Chalermsri et al, 2022;Choudhury & Headey, 2018), while Otunchieva et al (2022) found a lower dietary diversity score (DDS) among urban women. Though Aberman et al (2022) reported that urban agriculture enables women to contribute to household food security and dietary diversity, Pandey et al (2020) found that urbanization may not improve food diversification due to low income, increased reliance on food purchases, and a shift in food preferences toward high sugary and instant food.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies mentioned that dietary diversity in urban areas is higher compared to rural (Chalermsri et al., 2022 ; Choudhury & Headey, 2018 ), while Otunchieva et al. ( 2022 ) found a lower dietary diversity score (DDS) among urban women. Though Aberman et al.…”
Section: Introductionmentioning
confidence: 99%